READING THE DEAD WITH W.G. SEBALD: relational challenges to neoliberalism. Issue 3 (4th May 2019) - Carter, Josephine
Abstract: Subject to the ruthless accountancy of the neoliberal university, the humanities are under increasing pressure to make a case for why they count. This article focuses on how the field of literary criticism can advance a form of reading that destabilises neoliberalism's bedrock: the autonomous subject. This form of reading requires closely scrutinising modes of literary interpretation that implicitly privilege the neoliberal account of ethics, which reduces responsibility to a matter of autonomous individuals calculating their culpability. In turn, this form of reading carefully attends to texts that invoke a model of Levinasian ethical responsibility which is constituted through our relations with others. Using W.G. Sebald's work The Emigrants as a case study, I show how encounters with the deaths of others can invoke the relational indebtedness that is both inherent to the subject's constitution and the basis of its responsibility for others. Through affirming a model of ethics founded on relationality and offering a mode of reading that can attend to such an ethics, literary criticism provides us with the opportunity to engage with our world anew. In the place of autonomous subjects, we discover creatures of relationality who emerge as indebted to, attuned to, and responsible for the living.